Prevalence, etiology, testicular function and clinic outcome before and after varicocelectomy: A systematic review - Maryam Mirchenari; Behzad Abbasi; Marziyeh Tavalaee; Leila Azadi; Mohammad-Hossein Nasr- Esfahani (مجله دانشگاه علوم پزشکی گرگان, 2019)
Varicocele is a deficiency of the testicular veins which is recognized by elongation and tortuosity of the pampiniform or cremasteric venous plexus and can lead to impaired spermatogenesis. Varicocele intensity is associated with the reduction of male fertility potential. This review article discusses the effects of varicocele on spermatogenesis process and fertility potential, etiology of varicocele, therapeutic approaches, and the result of treatment. All the published papers from 1975 to 2018 from databases bank such as Science Direct, Google Scholar, Scopus, and PubMed with keywords; infertility, varicocele, varicocelectomy, spermatogenesis, clinical outcome were collected and within these papers, only 74 papers were included for this study. Increased of testicular temperature, backflow of toxic metabolites from the kidney or adrenal glands, hypoxia, hormonal disturbances and oxidative stress are the most prevalent pathogenic cause of varicocele that they can alter testis and sperm functions. Several studies show that varicocelectomy can improve sperm parameters, chromatin statue and fertility potential in infertile men with varicocele. Possibly, treatment of varicocele before assisted reproduction technologies could increase the chance of spontaneous pregnancy in these infertile men.